Respon Peternak Sapi Potong Terhadap Keberhasilan Inseminasi Buatan Di Kabupaten Malang - Murti, Ariani Trisna; Suroto, Karunia Setyowati; Osi, Matilda (Jurnal Ilmiah Fillia Cendekia, 2024)
This study aimed to evaluate the farmers' responses to the successful implementation of artificial insemination (AI) technology in beef cattle cultivated in Wajak District, Malang Regency. The method used is a survey involving 100 beef cattle farmers as samples, where the characteristics of the samples used are having at least 3 years of farming experience and the number of samples owned between 2 to 7 heads. Based on the analysis, it was found that farmers' assessment of the role of inseminators, farmers' knowledge of artificial insemination technology, and farmers' assessment of the implementation of artificial insemination were in a good category and the level of satisfaction was very satisfactory.The application of artificial insemination technology has a big influence so it has a good impact on the development of beef cattle farming. The factor that has the highest influence is the variable of breeding experience owned by farmers. Breeding experience is an important factor in developing livestock businesses and greatly influences the successful application of artificial insemination technology. The longer experience farmers have in beef cattle farming, the broader the level of experience they have. This condition makes it effective and easy to implement motivation and innovation to develop beef cattle farming. Therefore, farming experience is a key factor in determining the success of implementing artificial insemination for beef cattle in the Wajak sub-district, Malang district.